EKOWISATA DALAM MENJAGA SISTEM KETAHANAN LINGKUNGAN DESA ENDE - Fitria Pitri; Samadi Samadi (Jurnal Green Growth dan Manajemen Lingkungan, 2017)
The village of Ende is a traditional hamlet located in Sengkol Village, Pujut Subdistrict, Central Lombok. These villagers live their daily activities by holding firmly to traditions that are still rooted from their ancestors. It is seen that the house thatched roofs that characterize the Sasak tribe would be an interesting scenery and become one of the attractions of tourists to come to the village. The purpose of this research is to know how effort done by sasak tribe in order to increase tourist attraction of Ende village and how social society role of society of Ende village to change its environment. This research uses qualitative descriptive method, through observation and interview. The results of this study indicate that the village of Ende as a tourist village has some efforts or ways that are done in order to improve the tourist attraction. The method used is inseparable from the rules and norms that apply in the village of Ende. This norm is of course based on local wisdom while maintaining the authenticity of their customs. In addition to the customary norms governing, there is also the social role of the Sasak people to preserve the culture and environment of Ende Village from the diffusion of foreign cultures.